RANCANG BANGUN SISTEM PENGENDALIAN TEKANAN UAP AIR PADA TABUNG BOILER DENGAN PLC CIMON CM3-SP32MDTF-SD - Ramadan, Ilham; Mamesah, Chrestian Maxi (Jurnal Mahasiswa Terapan; Vol 1 No 1 (2024): Jurnal Mahasiswa Terapan, 2024)
Boilers are important devices in various power plants and industries to produce steam used in the process. One of the critical aspects of boiler operation is the precise control of steam pressure to ensure operational efficiency and safety. This assignment discusses the design of a steam pressure control system in a boiler tube with a CIMON CM3-SP32MDTF-SD PLC. The purpose of this study is to design an automatic control system that can maintain the steam pressure in the boiler stable according to the predetermined setpoint. This system uses a pressure sensor to read steam pressure in real-time and send data to the PLC. Thus, this system can maintain stable steam pressure within safe limits and according to process needs. The methods used in this study include system requirements analysis, hardware design, development of a control program with a CIMON CM3-SP32MDTF-SD PLC, and system testing and calibration. The results of the system implementation show that the steam pressure control system with the CIMON CM3-SP32MDTF-SD PLC is able to maintain stable steam pressure in the desired range. In addition, this system has automatic water level control to improve boiler operational efficiency and safety with fast response capability to pressure changes.